Duplex Electrochemical DNA Sensor to Detect Bacillus anthracis CAP and PAG DNA Targets Based on the Incorporation of Tailed Primers and Ferrocene-Labeled dATP - Magriñá, Ivan; Jauset-Rubio, Miriam; Ortiz, Mayreli; Tomaso, Herbert; Simonova, Anna; Hocek, Michal; O'Sullivan, Ciara K (ACS omega, 2019)
We report the duplex amplification of two plasmid DNA markers involved in the virulence of Bacillus anthracis, CAP and PAG, and the direct electrochemical detection of these amplicons. The method consists of the simultaneous amplification of the two targets in a single-pot reaction via polymerase chain reaction (PCR) using tailed primers and ferrocene-labeled dATP. Following amplification, the PCR products hybridize to probes immobilized on electrodes in a microfabricated electrode array chip. The incorporated ferrocene labeled dATP is then detected using square wave voltammetry. We evaluated the effect of electrolyte cations, anions, and concentration to condense, bend, and shrink double-stranded DNA and their effect on the intensity of the ferrocene signal. We obtained detection limits of 0.8 and 3.4 fM for CAP and PAG targets, respectively. We successfully developed a method to detect the presence of both targets in genomic DNA extracted from real samples.